Effects of ischemic preconditioning on economy, VO2 kinetics and cycling performance in endurance athletes - Kilding, A. E.; Sequeira, G. M.; Wood, M. R. (European Journal of Applied Physiology, 2018)
The aim of this study was to determine the effect of ischemic preconditioning (IPC) on several measures of aerobic function and 4-km cycling time-trial performance. An acute cross-over design was adopted involving eight well-trained cyclists (age 27.0 ± 7.0 years) who completed incremental and square-wave exercise tests for determination of peak O2 uptake (VO2peak), ventilatory threshold (VT) and moderate- and heavy-intensity domain VO2 kinetics, as well as 4-km time trials. All were preceded by IPC, or sham-IPC, involving repeated bouts of thigh blood flow occlusion, interspersed with reperfusion. There was no significant difference between IPC and sham-IPC with respect to VO2peak (4.4 ± 0.6 L/min vs 4.4 ± 0.5 L/ min, effect size - 0.01 ± 0.09), VT (3.4 ± 0.6 L/min vs 3.5 ± 0.5 L/min), effect size 0.07 ± 0.28), cycling economy (4.9 ± 4.9%, ES 0.24 ± - 0.24, P > 0.05) or any moderate-domain VO2 kinetic parameter. During heavy-intensity exercise, a reduced end-exercise VO2, slow component amplitude and overall gain was observed following IPC compared to sham-IPC. Though not statistically significant, there was a possibly beneficial effect of IPC on 4-km time-trial mean power output (2.2 ± 2.0%; effect size: 0.18 ± 0.15, P > 0.05). The observed reduction in VO2 slow component and tendency for improved economy and 4-km time-trial performance, albeit small, suggests that acute IPC shows some potential as a performance-enhancing priming strategy for well-trained cyclists prior to high-intensity exercise.